Permafrost research: monitoring through a sensors network at the "Istituto Mosso" LTER site (Col d'Olen, Aosta Valley, Italy) - COLOMBO, NICOLA; FRATIANNI, SIMONA; GUENZI, DIEGO; ACQUAOTTA, FIORELLA; GIARDINO, Marco; PEROTTI, Luigi; FREPPAZ, Michele; GODONE, DANILO FRANCESCO; SAID PULLICINO, DANIEL; MARTIN, Maria; VIGLIETTI, DAVIDE; ISAIA, MARCO; et al. (CNR - IMATI, 2014)
Permafrost is a specific ground thermal condition and rock glaciers are the most prominent geomorphic features of alpine permafrost. Atmospheric warming is likely to have strong impacts on permafrost, making cold areas at high elevation especially vulnerable. Therefore, climatic evolution and its impact on abiotic and biotic components of permafrost environments is a research topic of increasing importance. An integrated research and monitoring site on alpine permafrost has been set up in the active Col d'Olen rock glacier as a contribution to the Italian network of Long Term Ecological Research (LTER-Italia). Climatic data from manned and automatic weather stations have been already collected in the study area and they will be updated and analysed in the future. Moreover, a network of portable instruments has been established on the rock glacier's body for collecting meteorological data, after a dedicated calibration to assess the uncertainties of the measures, in the context of the collaboration with MeteoMet2. The physical and chemical characteristics of the rock glacier outflow are under investigation by using temperature dataloggers and a multi-parametric probe spectro::lyser. Regular sampling of water (on weekly basis) has been also established for investigating major ion concentrations, trace elements and isotopic analyses. Moreover, the physical and chemical characteristics of finegrained material are under analysis. The ground surface temperature monitoring will be conducted using Maxim iButton DS1922L mini-thermocrons and Hobo TidbiTv2 temperature loggers, regularly distributed on the rock glacier's surface and in a few selected surrounding sites. Total station and differential phase GPS will allow an accurate grid distribution and to acquire the coordinates of the dataloggers. In addition, high-resolution digital terrain models and thermal images of the rock glacier area will be obtained using a terrestrial laser scanner and an unmanned aerial vehicle (UAV). Finally, ground-dwelling arthropod ...